Risk Mitigation of Inventory Discrepancies in Spare Parts Warehouse Using RCA–FMEA–QFD Approach: A Case Study at PT XYZ - Ferdira, Novri Oekma; Santoso, Filiana; Baskoro, Gembong (Program Studi Teknik Industri, Fakultas Teknik, Universitas Muhammadiyah Palembang, 2025)
This study addressed the issue of inventory discrepancies in the spare parts warehouse of PT XYZ, which previously recorded a discrepancy rate of 0.94% in 2024. The objective was to design and evaluate a mitigation strategy to reduce the discrepancy rate to 0.5%. An integrated approach combining Root Cause Analysis (RCA), Failure Mode and Effect Analysis (FMEA), and Quality Function Deployment (QFD) was applied. RCA identified human error, inaccurate recording, and weak monitoring as the dominant causes of discrepancies. FMEA results showed that stock visibility, accuracy of receiving, and shipping errors were the most critical risks. QFD analysis further revealed that three technical requirements—real-time stock visibility, 100% receiving accuracy, and the penalty system—contributed most significantly to discrepancy reduction. The implementation of these requirements reduced the discrepancy rate from 0.94% to 0.5% between January 2024 and May 2025. Pearson correlation analysis confirmed that these factors had strong positive relationships with customer requirements and discrepancy reduction, with correlation coefficients above 0.7. These findings demonstrated that the integrated RCA–FMEA–QFD approach not only reduced discrepancies but also improved process reliability and operational performance in warehouse management.